THE MONOCLINIC I2 STRUCTURE OF BASSANITE, CALCIUM SULFATE HEMIHYDRATES (CASO4∙0,5H2O) - Ballirano P.; Maras A.; Meloni S.; Caminiti R. (My University, 2001)
A structural analysis of CaSO4 . 0.5H(2)O, a dehydration product of gypsum, has been carried out through the Rietveld method on X-ray powder diffraction data. A dehydrated powder of synthetic gypsum has been charged inside a non-hermetically sealed capillary in order to allow a slow rehydration. The starting material has been identified as gamma -anhydrite, space group P6(2)22, cell parameters a = 6.9691(2) Angstrom, c=6.3033(2) Angstrom. The final product of the rehydration of gamma -anhydrite is CaSO4 . 0.5H(2)O, space group I2 (unique axis b), cell parameters a = 12.0350(5) Angstrom, b = 6.9294(3) Angstrom, c = 12.6705(4) Angstrom, beta = 90.266(3)degrees. The structure of the hemihydrate is strongly pseudo-trigonal, space group P3(1)21. The symmetry lowering arises from water molecules ordering inside the channels.
Keywords: γ-anhydrite; CaSO4·0.5H2O; bassanite; gypsum; X-ray powder diffraction; Rietveld method